Gastrointestinal stromal tumors in kidney transplant recipients: Report of two cases and literature review. Issue 1 (27th July 2016) - Cheung, Chi Yuen; Lo, Stanley Hok King; Chan, Ching Kit; Li, Fu Keung; Cheng, Ignatius Kum Po; Chau, Ka Foon
Abstract: Gastrointestinal stromal tumors (GISTs) are the most common primary mesenchymal gastrointestinal neoplasms. However, GISTs occurring in kidney transplant recipients, including their treatment and outcome, are rarely described in literature. We hereby report two kidney transplant recipients with GISTs. Our first patient was diagnosed with high‐risk epithelioid gastric GIST 2 years after kidney transplant. He received everolimus after resection and remained disease‐free for 2 years before liver metastasis was confirmed. Imatinib therapy was planned but he died of fulminant pneumonia shortly. Our second patient was diagnosed with spindle cell GISTs in the mesentery 1 year after kidney transplant. Only partial response was obtained with imatinib as new lesions continued to develop. Withdrawal of cyclosporine and introduction of sirolimus resulted in complete shrinkage of existing tumors and no new lesions. He remained disease‐free for more than 10 years. Combination therapy consisting of imatinib and inhibitors of mammalian target of rapamycin (mTORi) seems to be safe and effective in kidney transplant recipients. However, therapeutic drug monitoring of mTORi is essential to avoid nephrotoxicity. Further trials addressing the optimal dosage of imatinib and mTORi in kidney transplant recipients are recommended.